Integrated care for people experiencing homelessness: changes in emergency department use and behavioral health symptom severity - Lexie R. Grove; Justin K. Benzer; Maria F. McNeil; Tim Mercer (BMC Health Services Research)
Abstract Background Health care for individuals experiencing homelessness is typically fragmented, passive, reactionary, and lacks patient-centeredness. These challenges are exacerbated for people who experience chronic medical conditions in addition to behavioral health conditions. The objective was to evaluate an innovative healthcare delivery model (The Mobile, Medical, and Mental Health Care [M3] Team) for individuals experiencing homelessness who have trimorbid chronic medical conditions, serious mental illness, and substance use disorders. Methods We assessed changes in study measures before and after M3 Team enrollment using multi-level mixed-effects generalized linear models. Data sources included primary data collected as part of the program evaluation and administrative records from a regional health information exchange. Program participants continuously enrolled in the M3 Team between August 13, 2019 and February 28, 2022 were included in the evaluation (N = 54). The M3 Team integrates primary care, behavioral health care, and services to address health-related social needs (e.g., Supplemental Nutrition Assistance Program benefits and Social Security/Disability benefits). Outcome measures included number and probability of emergency department (ED) visits and behavioral health symptom severity measured using the Behavior and Symptom Identification Scale (BASIS-24) and the Addiction Severity Index (ASI). Results M3 Team participants experienced a decrease of 2.332 visits (SE = 1.051, p < 0.05) in the predicted number of ED visits in a 12-month follow-up period, as compared to the 12-month pre-enrollment period. M3 Team participants also experienced significant reductions in multiple domains of mental health symptoms and functioning and alcohol and drug use severity. Conclusions Individuals experiencing homelessness who received integrated, patient-centered care from the M3 Team saw reductions in ED use and improvements in aspects of self-reported psychosocial functioning and substance use symptoms after enrollment in this novel healthcare delivery model.